Effect of limestone, lignite and biochar applied alone and combined on cadmium uptake in wheat and rice under rotation in an effluent irrigated field. (August 2017) - Rehman, Muhammad Zia ur; Khalid, Hinnan; Akmal, Fatima; Ali, Shafaqat; Rizwan, Muhammad; Qayyum, Muhammad Farooq; Iqbal, Muhammad; Khalid, Muhammad Usman; Azhar, Muhammad
Abstract: Cadmium (Cd) uptake and accumulation in crop plants, especially in wheat ( Triticum aestivum ) and rice ( Oryza sativa ) is one of the main concerns for food security worldwide. A field experiment was done to investigate the effects of limestone, lignite, and biochar on growth, physiology and Cd uptake in wheat and rice under rotation irrigated with raw effluents. Initially, each treatment was applied alone at 0.1% and combined at 0.05% each and wheat was grown in the field and then, after wheat harvesting, rice was grown in the same field without additional application of amendments. Results showed that the amendments applied increased the grain and straw yields as well as gas exchange attributes compared to the control. In both crops, highest Cd concentrations in straw and grains and total uptake were observed in control treatments while lowest Cd concentrations was observed in limestone + biochar treatment. No Cd concentrations were detected in wheat grains with the application of amendments except limestone (0.1%). The lowest Cd harvest index was observed in limestone + biochar and lignite + biochar treatments for wheat and rice respectively. Application of amendments decreased the AB-DTPA extractable Cd in the soil while increasing the Cd immobilization index after each crop harvest. The benefit-cost ratio and Cd contents in plants revealed that limestone + biochar treatment might be an effective amendment for increasing plant growth with lower Cd concentrations. Graphical abstract: Highlights: Limestone, lignite and biochar increased straw and grain yield of both wheat and rice. All amendments reduced the cadmium (Cd) uptake in wheat and rice. Lowest Cd in straw and grains was observed with the limestone + biochar application. All amendments increased the Cd immobilization index after wheat and rice harvest. The limestone + lignite had the highest benefit-cost ratio compared to other amendments. Abstract : Field application of amendments reduced the Cd concentrations in wheat and rice.